Fitness-to-drive after mild traumatic brain injury: Mapping the time trajectory of recovery in the acute stages post injury. (June 2015) - Baker, Anne; Unsworth, Carolyn A.; Lannin, Natasha A.
Highlights: Two groups of participants were recruited: patients with a mTBI and a control group. Both groups were assessed at 24 h post injury on assessments of fitness-to-drive. Follow-up occurred at two weeks post injury to establish driver status. This research confirms that patients with a mTBI should not to drive for 24 h. Further research is required to map factors which facilitate timely return to driving. Abstract: Introduction: Little is known about the trajectory of recovery in fitness-to-drive after mild traumatic brain injury (mTBI). This means that health-care professionals have limited evidence on which to base recommendations to this cohort about driving. Objective: To determine fitness-to-drive status of patients with a mTBI at 24 h and two weeks post injury, and to summarise issues reported by this cohort about return to driving. Method: Quasi-experimental case-control design. Two groups of participants were recruited: patients with a mTBI ( n  = 60) and a control group with orthopaedic injuries ( n  = 60). Both groups were assessed at 24 h post injury on assessments of fitness-to-drive. Follow-up occurred at two weeks post injury to establish driver status. Main Measures: Mini mental state examination, occupational therapy-drive home maze test (OT–DHMT), Road Law Road Craft Test, University of Queensland-Hazard Perception Test, and demographic/interview form collected at 24 h and at two weeks. Results: At the 24 h assessment, only the OT–DHMT showed a difference in scores between the two groups, with mTBI participants being significantly slower to complete the test ( p  = 0.01). At the two week follow-up, only 26 of the 60 mTBI participants had returned to driving. Injury severity combined with scores from the 24 h assessment predicted 31% of the variance in time taken to return to driving. Delayed return to driving was reported due to: "not feeling 100% right" ( n  = 14, 23%), headaches and pain ( n  = 12, 20%), and dizziness ( n  = 5, 8%). Conclusion: This research supports existing guidelines which suggest that patients with a mTBI should not to drive for 24 h; however, further research is required to map factors which facilitate timely return to driving.